Does Moral Identity Matter in Situational Action Theory? Some Evidence of Iranian Fans’ Cyberbullying Perpetration - Kabiri, Saeed (International criminal justice review, 2020)
Situational action theory (SAT) posits that morality plays a core role in determining whether situations are viewed as suitable for crime. However, little attention has been paid to moral identity, the degree to which a person considers morality to occupy a central position in their view of themselves. Using a convenience sample of Iranian soccer fans (N = 374), we test both the direct and moderated role of moral identity in explaining cyberbullying, an outcome that differs from most SAT research focusing on violent/property crime. We find that fans with a weaker moral identity tend to engage in more cyberbullying and that moral identity significantly interacts with a number of SAT-derived predictors (moral emotions, self-control, perceptual deterrence, and situational morality) in expected ways.